5-Hydroxymethyl-2-Furfural Oxidation Over Au/CexZr1-xO2 Catalysts - Megías-Sayago, Cristina; Bonincontro, Danilo; Lolli, Alice; Ivanova, Svetlana; Albonetti, Stefania; Cavani, Fabrizio; Odriozola, José A. (Frontiers in Chemistry, 2020)
A series of gold catalysts supported on pure CeO2, ZrO2 and two different Ce-Zr mixed oxides have been prepared and tested in the 5-hydroxymethyl-2-furfural oxidation reaction. All catalysts show high catalytic activity (100% conversion) and important selectivity (27-41%) to the desired product i.e. 2,5-furandicarboxylic acid at low base concentration. Products selectivity changes with the support nature as expected, however, the observed trend cannot be related neither to gold particle size, nor to catalyst reducibility and oxygen mobility. An important relation between the FDCA selectivity and the support textural properties is observed, conducing to the general requirement for optimal pore size for this reaction.